Can we predict ectotherm responses to climate change using thermal performance curves and body temperatures? - Sinclair, Brent J.; Marshall, Katie E.; Sewell, Mary A.; Levesque, Danielle L.; Willett, Christopher S.; Slotsbo, Stine; Yunwei, Dong; Harley, Christopher D. G.; Marshall, David J.; Helmuth, Brian S.; Huey, Raymond B. (John Wiley & Sons Ltd/CNRS, 2016)
Thermal performance curves (TPCs), which quantify how an ectotherm’s body temperature (Tb ) affects its performance or ﬁtness, are often used in an attempt to predict organismal responses to climate change. Here, we examine the key – but often biologically unreasonable – assumptions underlying this approach; for example, that physiology and thermal regimes are invariant over ontogeny, space and time, and also that TPCs are independent of previously experienced T b. We show how a critical consideration of these assumptions can lead to biologically useful hypotheses and experimental designs. For example, rather than assuming that TPCs are ﬁxed during onto- geny, one can measure TPCs for each major life stage and incorporate these into stage-speciﬁc ecological models to reveal the life stage most likely to be vulnerable to climate change. Our over- all goal is to explicitly examine the assumptions underlying the integration of TPCs with T b ,to develop a framework within which empiricists can place their work within these limitations, and to facilitate the application of thermal physiology to understanding the biological implications of climate change.